(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: Even with the recent creation of "Temurbeklar maktabi," militaryacademic lyceums, there are still problems with teaching and mastering foreign languages inside this military educational system. The difficulties that come with teaching foreign languages to students in these military academic lyceums will be discussed in this article. It will also offer practical ideas for improving foreign language instruction, like task- and inquiry-based learning approaches. The paper will highlight the applicability of these techniques for teaching military students and go into detail on how to use them effectively in the classroom. The article highlights the significance of these methods and claims that they are especially helpful for enhancing oral communication skills, such as speaking and listening capacities.